2017
DOI: 10.1159/000452493
|View full text |Cite
|
Sign up to set email alerts
|

Space and Objects: On the Phenomenology and Cognitive Neuroscience of Anomalous Perception in Schizophrenia (Ancillary Article to EAWE Domain 1)

Abstract: Background/Aims: Perception of space and objects is a traditional focus within phenomenology, and disturbances in these aspects of perception among people with schizophrenia have long been discussed within phenomenological psychiatry. Despite this, there has been little empirical work on the causes and effects of most of these perceptual alterations in people with schizophrenia. Progress towards this goal can be accelerated by the use of EAWE (Examination of Anomalous World Experience), an interview-based tool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…29–31 Perceptual fragmentation is associated with worse outcomes, 31 and may contribute to figure-ground confusion and loss of perceptual stability, with objects appearing to change shape or appearance. 32,33 Persons with these visual distortions are also more likely to experience visual hallucinations, 34 possibly pointing to shared processes contributing to these phenomena. These lines of research suggest that sensory and perceptual anomalies, including perceptual disorganization, may be implicated in phenomena that meet criteria for hallucinations, and investigation of these changes and the processes involved may shed light on the development of hallucinations.…”
Section: Domains Of Experiencementioning
confidence: 99%
“…29–31 Perceptual fragmentation is associated with worse outcomes, 31 and may contribute to figure-ground confusion and loss of perceptual stability, with objects appearing to change shape or appearance. 32,33 Persons with these visual distortions are also more likely to experience visual hallucinations, 34 possibly pointing to shared processes contributing to these phenomena. These lines of research suggest that sensory and perceptual anomalies, including perceptual disorganization, may be implicated in phenomena that meet criteria for hallucinations, and investigation of these changes and the processes involved may shed light on the development of hallucinations.…”
Section: Domains Of Experiencementioning
confidence: 99%
“…Visual hallucinations are not the only form of visual perceptual anomaly experienced in schizophrenia. For example, over 60% of people with schizophrenia experience visual distortions involving changes in clarity, form, brightness, color, motion, or persistence of visual stimuli (8,(12)(13)(14)(15)(16)(17)(18) (see Table 1). It has also been reported that visual imagery is increased in people with schizophrenia (19).…”
Section: Introductionmentioning
confidence: 99%
“…Characterizing abnormalities in the predictions that derive from different types of prior sensory experiences and in their influence on current visual perception, then, has the potential to provide a nuanced and biologically-informed perspective on prediction abnormalities in psychosis generally, but also stands to inform etiological conceptualizations of the subjective alterations in visual perception reported by individuals with schizophrenia more specifically (e.g. Freedman and Chapman, 1973;Silverstein et al, 2017). Experimental evidence for such perceptual alterations comes from a range of tasks (reviewed in Butler et al, 2008;Chen, 2011;Silverstein, 2016;Skottun and Skoyles, 2007;Yoon et al, 2013), and a role of abnormal prediction in these alterations has previously been proposed (Silverstein, 2016).…”
Section: Introductionmentioning
confidence: 99%